SIFAT MEKANIK PAPAN GYPSUM DARI SERBUK LIMBAH KAYU NON KOMERSIAL - Saibatul Hamdi (Jurnal Riset Industri Hasil Hutan, 2014)
The purpose of this research is to know the mechanical strength of gypsum board by utilizing waste sawn wood. Raw materials used consist of flour, gypsum,wood particles, boraks and kambang (Goniothalamus sp), wood tarap (Artocarpus elasticus REINW) and lua (Ficus glomerata ROXB). Wood particle 40 mesh and 60 mesh, concentrations boraks of 1 and 2 and the percentage particles of gypsum sawn timber is 300, 400 and 500%. The results showed that the average value Modulus of Rufture (MoR) in lua wood ranges from 12.55 – 14,47 kgcm2, wood kambang 25.10-31,11 kgcm2 and wood tarap 19.20- 24,18 kgcm2. As for Modulus of Elasticity (MoE) on the lua 1129,80- 2092,70 kgcm2, wood kambang 2512,37-3971,32 kgcm2 and tarap 2050,63-2691,09 kgcm2. Gypsum board are mechanical properties do not meet quality standards created SNI 03-6434-2000.Keywords: sawdust, lua, kambang, tarap, gypsum, mechanical